Effects of economic regional differences and family on adolescents' aggressive behaviors: Perspective of ecosystem integration. Issue 2 (27th December 2022) - Hong, Xinwei; Liu, Shen; Fan, Hang; Xie, Hongwei; Fang, Shengjie; Zhang, Lin
Abstract: Introduction: Based on the ecological systems theory and cumulative risk model, the current study aimed to determine the mediating effects of parenting styles, peer relationship, and psychological capital on family socioeconomic status and adolescents' aggressive behaviors, as well as the moderating effects of economic regional differences. Methods: In a cross‐sectional design, 1271 Chinese adolescents were recruited to complete the MacArthur Scale, the short‐form Egna Minnen av Barndoms Uppfostran, the Positive PsyCap Questionnaire, the peer support subscale in the Student Personal Perception of Classroom Climate, and the Aggression Questionnaire. Results: After controlling for gender and age, parenting style, peer relationship, and psychological capital not only mediated, but also constituted multiple chains mediation between family socioeconomic status and aggressive behaviors. Moreover, economic regional differences moderated the multiple chains mediation model between family socioeconomic status and aggressive behaviors. Conclusion: The accumulation of multiple adverse factors increases the probability of inducing aggressive behaviors, and the development of psychological capital helps reduce the occurrence of aggressive behaviors in adolescents. Abstract :